ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGANGGURAN DI KABUPATEN/KOTA WILAYAH SARBAGITA - Haribawani, Putu Nanda; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.09.TAHUN.2021, 2021)
This study aims to analyze the effect of investment, minimum wages, contribution of the tertiary sector, and economic growth simultaneously and partially on the level of open unemployment in the Regency / City of the Sarbagita Region. This study uses panel data, namely a combination of time series data (2011-2019) and cross section (four districts / cities in the Sarbagita area) with a total of 36 observations. The data collection method is done through observation with secondary data. The analysis technique used in this research is multiple linear regression analysis. The results showed that investment, minimum wages, contribution of the tertiary sector, and economic growth simultaneously had a significant effect on the level of open unemployment in the district / city of the Sarbagita region. Partially, investment has a positive effect and minimum wages have a negative and significant effect on the open unemployment rate in the Regency / City of the Sarbagita Region, while the contribution of the tertiary sector and economic growth does not have a significant effect on the level of open unemployment in the Regency / City of the Sarbagita Region with the coefficient of the tertiary sector contribution positive direction and negative economic growth.